Caracterização de rezas populares no município de Itabaiana-SE : uma análise sociodiscursiva - Carvalho, José Carlos Andrade (2015)
The work called "Characterization of popular prayers in the city of Itabaiana-SE: A socio-discursive analysis” describes the socio-historical process of a heritage of oral culture, popular prayers. We also analyze linguistic elements present in several illustrative prayers. Richness of a culture that, by oral routes, will be transmitted from generation to generation. Twenty agents of popular piety were surveyed, domiciled, principally in the villages of the northern region of the country. These people intone prayers for needy believers seeking healing or protection for physical and spiritual ills. The social profile and the historicity of such agents who enjoy a certain prestige for the work carried out in the communities were raised. The theoretical framework refers to the works of Luiz Câmara Cascudo, Marilena Chauí, Eduardo Hoornaert, Gilmário Moreira Brito, Luiz Antonio Marcuschi, Carlos Rodrigues Brandão, Paul Zumthor, Pierre Bourdieu, Michel Foucault, among others. This research also documents of the oral memory of local residents on the agenda, contributing certainly to the written record of the collection of religious culture, doomed to gradual extinction, to the extent that the holders are disappearing.